Destination Attributes dan Implikasi Kebijakan Manajemen Daya Tarik MICE di Indonesia - Nining Yuniati (CV. Ulil Albab Corp, 2023)
This paper is a semi-systematic literature review because it combines several studies at once with a qualitative review. There are a number of previous studies that have found a number of attributes that are criteria in determining the best MICE destinations. However, every researcher has their own point of view, even though in absolute terms most of the opinions have almost the same major criteria. In Indonesia, a number of these studies were later adapted and rolled out in the form of policies whose purpose is to provide guidelines for regions throughout Indonesia so that they are able to develop their regions into good MICE destinations. There is no clear reference which is best, but in the case of Indonesia, the official regulations set by the government are very good to implement